Estudo de efeitos quânticos em redes de junções Josephson SNS e SIS com composição Nb-CuxAlyOz-Nb através da indução de vórtices por conseqüência do tamanho de rede - Rivera, Victor Anthony Garcia (2009)
In this thesis we studied the quantum effects in networks of Josephson junctions under the induction of vortices and as a consequence of the size of the sample itself. For this, it also was carried out all the instrumentation required to achieve that goal. The superconducting devices known as Josephson junctions offer the opportunity to study a wide variety of concepts of basic physics, especially when they are in the form of twodimensional arrays called networks. In particular, these structures allow us to study quantum phenomena such as tunneling Josephson dc / ac, proximity effect, Coulomb blockade, quantum fluctuations and others like phase transition of Berezinsky-Kosterlitz-Thouless (BKT), all present in these devices. In particular, in this thesis we study two-dimensional networks of Josephson junctions of types SNS (superconductor-normal-superconductor) and SIS (superconductor-insulatorsuperconductor) with composition Nb -CuxAlyOz-Nb. The study of these samples was performed by obtaining the characteristic curves V × I with and without applied magnetic field. The analysis of these curves was performed by the law of power scale: for the SNS network, and / for the SIS networks. The fact that two types of formulas adjustment is due to the asymptotic behavior present in these samples. Moreover, the temperature of the BKT transition was determined for 3. The analysis of the experimental obtained results clearly shows the dependence of quantum effects on the size of the samples studied.